2002
DOI: 10.1046/j.1365-313x.2002.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

High free‐methionine and decreased lignin content result from a mutation in the Arabidopsis S‐adenosyl‐L‐methionine synthetase 3 gene

Abstract: SummaryAs an approach to understand the regulation of methionine (Met) metabolism, Arabidopsis Met overaccumulating mutants were isolated based on their resistance to selection by ethionine. One mutant, mto3, accumulated remarkably high levels of free Met ± more than 200-fold that observed for wild type ± yet showed little or no difference in the concentrations of other protein amino-acids, such as aspartate, threonine and lysine. Mutant plants did not show any visible growth differences compared with wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
153
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 42 publications
8
153
0
Order By: Relevance
“…SAMS, HMT, and SAH are some of the most abundant ESTs found in cDNA libraries made from immature xylem tissue of loblolly pine undergoing compression wood formation (M. Kirst, unpublished data), a tissue with high lignin content relative to normal wood. The underexpression of SAMS has been shown to result in a decrease of lignin content in maize (Zea mays; Shen et al, 2002). The coordination of transcript profiles is consistent with the importance of the shikimate and Met pathways in lignin biosynthesis and suggests that transcription of many of the genes in these pathways are under a higher level of coordinated control.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…SAMS, HMT, and SAH are some of the most abundant ESTs found in cDNA libraries made from immature xylem tissue of loblolly pine undergoing compression wood formation (M. Kirst, unpublished data), a tissue with high lignin content relative to normal wood. The underexpression of SAMS has been shown to result in a decrease of lignin content in maize (Zea mays; Shen et al, 2002). The coordination of transcript profiles is consistent with the importance of the shikimate and Met pathways in lignin biosynthesis and suggests that transcription of many of the genes in these pathways are under a higher level of coordinated control.…”
Section: Discussionmentioning
confidence: 54%
“…Genetic mapping of candidate genes identified in this study revealed genetic colocalization of SAMS with growth and lignin gene expression QTLs. SAMS' role as the last enzyme in the synthesis of S-adenosylmethionine and its negative effect on the levels of lignin in transgenic maize plants (Shen et al, 2002) suggest that it is an important candidate for further analysis. SAMS may represent a rate-limiting step in lignin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several associations were identified (mainly with sugar release efficiency) for genes involved in cysteine and methionine metabolism, including ATCIMS/MS1. The roles of these genes in biomass formation are becoming increasingly revealed, being linked directly to either lignin (50,51) or hormone-mediated growth regulation (52). In addition, SCW polysaccharide biosynthesis genes known to be expressed in developing xylem (8) were mainly associated with variation in wood density and glucose release efficiency (Dataset S3).…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation of Thr synthase leads to an imbalance in the regulation of the synthesis of aspartate-derived amino acids (Galili, 1995). Interestingly, even when the total concentration of SAM was increased or decreased in plant cells, plastid Thr synthase was not affected (Shen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%